Generation Z Work Experience In The Digital Workplace - Heskyel Pranata Tarigan (Journal of Business Management, 2026)
This study aims to explore and deeply understand the work experience of Generation Z (Gen Z) in the digital workplace, particularly in the local online media environment of bengkuluekspress.com. Generation Z, born between 1997 and 2012, is the first generation to grow up entirely within a digital ecosystem, making how they interpret, navigate, and respond to the digital work environment a compelling and important subject of inquiry. This research employs a qualitative approach using Moustakas's (1994) phenomenological method, which focuses on uncovering the essence of the lived experiences of informants. Data were collected through in-depth interviews, participatory observation, and documentation. Informants consisted of seven Gen Z employees of bengkuluekspress.com selected through purposive sampling. The findings reveal three main themes from Gen Z's work experiences: (1) rapid adaptation to digital technology as the primary capital, (2) work flexibility as a highly valued yet challenging principle, and (3) the search for meaning and professional identity amid the pressures of digital information speed. These findings contribute significantly to understanding the dynamics of the digital generation workforce and their implications for local digital media management.